Web-Based Satisfaction Survey Application for The State Polytechnic of Tanah Laut - Khairul Anwar Hafizd; Herpendi; Fathurrahmani; Muhammad Sabani Ackbar Ackbar (Sean Institute, 2022)
The State Polytechnic of Tanah Laut is a college located in Tanah Laut Regency, established on September 25, 2009. The college currently offers three majors: Informatics Engineering, Agricultural Industrial Technology, and Automotive Machinery, as well as one study program in Accounting. The current system at The State Polytechnic of Tanah Laut is semi-computerized, with many processes still relying on paper, such as the questionnaires used in the Learning Development Center and Education Quality Assurance Center (P4MP). The P4MP questionnaires are currently filled out using soft files in Microsoft Excel instead of paper sheets, but the process is still difficult for lecturers, students, and education staff and requires a significant amount of time for data recording. To address these issues, an application can be developed to assist in the process of filling out P4MP questionnaires at The State Polytechnic of Tanah Laut. The application will be web-based and designed using ERD (Entity Relationship Diagram), DFD (Data Flow Diagram), Flowchart, and will use the programming languages PHP and MySQL as the database.